Analysis and monitoring of mode transitions during afm nanomachining of IZO-Coated pyrex glass. Issue 1 (2nd January 2019) - Ahn, Yoomin; Lee, Seoung Hwan
ABSTRACT: The goal of this research is to investigate and monitor machining mode transitions during nanoscale scratching of IZO-coated Pyrex glasses using atomic force microscope (AFM). Among the AFM nanomachining mode features, which include elastic/plastic deformations and crack generation, pile-up (by ploughing) is a key surface phenomenon that can represent plastic deformation characteristics, such as a sign of chip making. Moreover, because the pile-up formation mechanism of coated materials is reported to be distinct from that of bulk materials, the examination of pile-up in coated materials is challenging, along with brittle transition (crack initiation). In this research, the pile-up formation and crack initiation, that occur during nanoscratching, were examined and analyzed near the coating-substrate (glass) boundary. In addition, acoustic emission (AE), a sensing scheme with nanoscale sensitivity, was introduced to detect significant machining state variations and mode transitions. Experimental and analysis results indicate that the proposed scheme is viable for characterizing/monitoring the nanoscale machining of coated materials.